In Vivo Effect of a Nisin-Biogel on the Antimicrobial and Virulence Signatures of Canine Oral Enterococci - Eva Cunha; Ana Filipa Ferreira; Sara Valente; Alice Matos; Luís Miguel Carreira; Marta Videira; Lélia Chambel; Luís Tavares; Manuela Oliveira (MDPI AG, 2023)
Periodontal disease is a relevant oral disease in dogs and nisin-biogel has been previously proposed to be used in its control. Enterococci, as inhabitants of the oral cavity with a high genetic versatility, are a reliable bacterial model for antimicrobial studies. Our goal was to evaluate the in vivo influence of the long-term dental application of the nisin-biogel on the virulence and antimicrobial signatures of canine oral enterococci. Twenty dogs were randomly allocated to one of two groups (treatment group-TG with nisin-biogel dental application, or control group-CG without treatment) and submitted to dental plaque sampling at day 0 and after 90 days (T90). Samples were processed for Enterococcus spp. isolation, quantification, identification, molecular typing and antimicrobial and virulence characterization. From a total of 140 enterococci, molecular typing allowed us to obtain 70 representative isolates, mostly identified as E. faecalis and E. faecium. No significant differences (p > 0.05) were observed in the virulence index of the isolates obtained from samples collected from the TG and CG at T90. At T90, a statistically significant difference (p = 0.0008) was observed in the antimicrobial resistance index between the isolates from the TC and CG. Oral enterococci were revealed to be reservoirs of high resistant and virulent phenotypes.